Oculofaciocardiodental Syndrome: A Rare Disorder with Canine Radiculomegaly - Aishwarya Rathod; Priyanka Jaiswal; Pankaj Banode; Gajendra Manakshe; Deepika Masurkar (Journal of Clinical and Diagnostic Research)
The ocular, face, dental, and cardiac systems are all impacted by the uncommon condition known as Oculofaciocardiodental (OFCD) syndrome. OFCD is only present in females due to its X-linked genetic inheritance and male embryonic lethality. The most common ailment in these patients is canine radiculomegaly. This particular feature highlights the role of dentists in detecting this syndrome. Accompanied with a report on a female patient with unique facial traits, we provide a comprehensive description of OFCD. In this case we have discussed with the typical features of OFCD. A 20-year-old female patient with OFCD syndrome presented with unique characteristics affecting ocular, cardiac, facial, and dental systems. Patient had congenital cataract, elongated roots of canine and incisors, elongated face with convex profile, cardiac abnormalities like atrial septal defect and ventricular septal defect. On the basis of clinical and radiographic findings and necessary medical diagnostic procedures, patient was diagnosed with OFCD syndrome. But due to lack of keen observation, the syndrome was undiagnosed and treatment was delayed. It is critical for every clinician to find out reasons and answers of abnormal finding in patient.